Analisis Respon Peserta Didik terhadap Penggunaan Google Classroom pada Pembelajaran Fisika - Sahlan, Sahlan (Jurnal Pendidikan Fisika dan Sains (JPFS), 2022)
The purpose of this study was to analyze the responses of students in the use of google classroom in physics learning. This study uses descriptive research with a quantitative approach. The data collection technique is through a questionnaire distributed to students of class XI MIPA odd semester for the 2021/2022 academic year at SMA Muhammadiyah Maumere using google form. Sampling in this study using simple random sampling. There were 20 students who participated in filling out the questionnaire so that all of them were used as samples. The research data were then analyzed descriptively quantitatively with the help of SPSS 25 software and Microsoft Excel to find the average student response to each question, while the percentage used Microsoft Excel. The results showed that on average, students responded to questionnaire questions with very positive criteria with an average of 84%, while an average of 70% with positive criteria, and 0 for negative and very negative criteria. The results of the analysis concluded that the use of google classroom media has a very positive impact on online physics learning.